Expression of platelet-bound stromal-cell derived factor-1 (SDF-1) and number of CD34+ progenitor cells in patients with congestive heart failure. (September 2014) - Jorbenadze, Rezo; Schleicher, Erwin; Bigalke, Boris; Stellos, Konstantinos; Gawaz, Meinrad
Abstract Platelet-bound stromal cell-derived factor-1 (SDF-1) plays a crucial role in attachment of circulating CD34+ progenitor cells to the vascular wall, facilitating tissue healing after injury. However there is no evidence about expression of platelet-bound SDF-1 in patients with congestive heart failure (CHF). The aim of our study was to evaluate expression of platelet-bound SDF-1 and number of CD34+ progenitor cells in patients with CHF. Forty-eight patients with idiopathic dilated cardiomyopathy (DCM) and 61 patients with ischaemic cardiomyopathy (ICM) were consecutively enrolled into the study. Blood taken from 109 consecutive patients was studied for surface expression of platelet-bound SDF-1 and number of CD34+ progenitor cells by flow cytometry. The highest expression of platelet-bound SDF-1 was observed in patients with severe impairment of left ventricular systolic function compared with patients with mild or moderate impairment of left ventricular systolic function (mild vs. moderate vs. severe impairment of left ventricular systolic function: MFI ± SD: 35.6 ± 34 vs. 101.45 ± 73 vs. 124.86 ± 86.7, Kruskal–Wallis p < 0.001). Similar to platelet-bound SDF-1 number of CD34+ progenitor cells was the highest in severe impairment of left ventricular systolic function (mild vs. moderate vs. severe impairment of left ventricular systolic function: mean ± SD: 260.4 ± 177.5 vs. 580.7 ± 340.5 vs. 640.82 ± 370.6, Kruskal–Wallis p < 0.001). Platelet-bound SDF-1 expression was associated with number of circulating CD34+ progenitor cells (r = 0.454, p < 0.001) in patients with CHF. Expression of platelet-bound SDF-1 and number of CD34+ cells were higher in patients with DCM compared with patients with ICM (p < 0.001 for both) and inversely correlated with age and aspirin therapy. Platelet-bound SDF-1 and CD34+ progenitor cells are especially increased in patients with severe impairment of left ventricular systolic function in CHF.